The Impact of BRT Systems on Local Economic Development: The Case of Meadowlands, Soweto - Ngobeni, Matimba (University of the Witwatersrand, Johannesburg, 2015)
Urban planners and transportation advocates around the world have become more innovative in confronting regional and global development concerns such as rapid urbanisation, congestion, urban sprawl, climate change, mounting infrastructure costs and high levels of urban poverty. In addressing these pressing issues, among many other policy advances, Local Economic Development and Transit Oriented Development have grown in popularity because they are considered important strategies in the notion of sustainable development. Due to the aforestated economic realities, environmental and social problems, most cities around the world support a change of transport modes in favour of efficient and sustainable mass transit options over private vehicles. As one example of this shift, BRT systems have become widely implemented. There are a wide-ranging reported socioeconomic and environmental benefits associated with BRT systems worldwide. This study focuses on the economic prospects they do offer in the context of Johannesburg. The central objective of this study is then to scrutinise the impacts the Johannesburg’s Rea Vaya BRT network has had on businesses and residents’ livelihoods in Meadowlands, Soweto. The study uses a single case study to deepen an understanding of how public transport improvements tend to influence social and economic development strategies in previously disadvantaged, emerging economy areas. The research is based on the critical analysis of literature on TOD and LED and qualitative interviews in Meadowlands and their critical analysis. A set of nuanced perspectives emerged on how the City of Johannesburg might formulate and carry out future TOD policy and projects as a way of effectively facilitating economic development through public interventions. Most pertinently, the study found that the operational Rea Vaya system in Meadowlands has improved access to social and economic opportunities. It has provided employment opportunities and triggered the development of Small, Medium and Micro-sized Enterprises. The provision of BRT services also diversified and improved mobility options in this area. However, affordability still remains a two-fold question among the BRT users and non-users.
Planning Honours Research Report 2015, Wits University
Keywords: BRT, Local economic development, transportation, businesses and residents, Meadowlands Soweto